2019
DOI: 10.1080/15592294.2019.1615357
|View full text |Cite
|
Sign up to set email alerts
|

Altered microRNA expression profiles in large offspring syndrome and Beckwith-Wiedemann syndrome

Abstract: The use of assisted reproductive technologies (ART) can induce a congenital overgrowth condition in humans and ruminants, namely Beckwith-Wiedemann syndrome (BWS) and large offspring syndrome (LOS), respectively. Shared phenotypes and epigenotypes have been found between BWS and LOS. We have observed global misregulation of transcripts in bovine foetuses with LOS. microRNAs (miRNAs) are important post-transcriptional gene expression regulators. We hypothesize that there is miRNA misregulation in LOS and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 91 publications
1
44
0
Order By: Relevance
“…MicroR-296-3p was previously reported to be expressed in ovaries in mice 60 and to repress cell plasticity in different tumour lines 61 , promoting apoptosis in liver 62 and in mammalian pancreatic α cells 63 . Recently, altered expression of bta-miR-296-3p was detected in muscle, kidney, and liver, in bovine foetuses with large offspring syndrome (LOS) 64 . In addition, miR-296 was also observed to be epigenetically regulated as a part of the imprinted Gnas/GNAS clusters 65 .…”
Section: Discussionmentioning
confidence: 99%
“…MicroR-296-3p was previously reported to be expressed in ovaries in mice 60 and to repress cell plasticity in different tumour lines 61 , promoting apoptosis in liver 62 and in mammalian pancreatic α cells 63 . Recently, altered expression of bta-miR-296-3p was detected in muscle, kidney, and liver, in bovine foetuses with large offspring syndrome (LOS) 64 . In addition, miR-296 was also observed to be epigenetically regulated as a part of the imprinted Gnas/GNAS clusters 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in cattle and sheep it has been noted a higher incidence of embryo loss, higher pregnancy length, large body size and birth weight in ART-derived gestations [25]. In addition, the large offspring syndrome described in cattle is an imprinting disorder with similar features to Beckwith-Wiedemann Syndrome in humans, such as macrosomia, macroglossia or visceromegaly [26,27]. Other anomalies observed in IVP-derived cattle due to an overgrowth in late gestation are a higher incidence of dystocia, hydrallantois, and neonatal mortality [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…In our attempt to investigate if the birth weight was affected by sex, we found that only females showed differences when the data were analysed separately, being the weight at birth higher in ET than in AI, as others reported [11], but such differences disappeared on days 3 and 15. This fact, however, should be kept in mind for future studies on the long-term phenotypes of ET animals because, as it has been shown in different studies, increased birth weight is one of the most common ndings in ARTderived calves and it has been related to the large offspring syndrome [24,25] as well as to the Beckwith-Wiedemann syndrome in humans [26], although it has not been described in pigs until now. Another reason not to obviate this nding is that the differences were observed only in females, which are the animals kept in the farm as future mothers for next generations.…”
Section: Discussionmentioning
confidence: 99%